Pre-harvest spray of salicylic acid to improve the quality and shelf life of ber fruit (Ziziphus mauritiana) - Kanwal, M Amna Jamil; Ahmad, Saeed; Nasir, Maryam; Jaskani, M J; Aziz, Maaz (Journal of Postharvest Technology, 2021)
Ber (Ziziphus mauritiana) is popular fruit among the poor community of Indo-Pak subcontinent. Vitamin A, B, C and essential minerals are major constituents of ber pulp. Pre-harvest drop and poor fruit quality are major problems of this fruit. Pre-harvest spray of salicylic acid (SA) directly or indirectly affects the oxidative metabolism and preserves the nutritional value of fruit during storage, following higher capacity to hold up oxidative injury. It also decreases the disease and pathogen attack. Therefore, an experiment was designed to find out the effect of foliar spray of SA on Ber. Two foliar sprays of Salicylic acid with different concentrations (1, 2 and 3 mM) were applied 30 and 15 days before harvesting. Plants sprayed with 1mM SA recorded higher fruit yield. Minimum fruit drop of 37.48% was noted in fruits of T1 (1 mM salicylic acid). Fruit length, diameter, color and weight were significantly higher in plants treated with 1mM SA as compared to non-treated ones. The highest TSS (9.57 °Brix), acidity (0.16%) Vitamin C (57.66 mg/100g) and total phenolics (263.93 mg GAE/100g), while, minimum seed weight of 0.78 g was observed in fruits of T3 (3 mM SA). Furthermore, the total sugars, reducing sugars and non-reducing sugars were significantly more in the treated fruits in comparison to untreated fruits. Hence, it is concluded that salicylic acid (1 mM) is effective to improve the quality of ber fruits (Ziziphus mauritiana).